Pre-service Teachers' Digital Experiences through Digital Pedagogical Practices in Norway - Jimarkon, Pattamawan; Wanphet, Phalangchok; Dikilitas, Kenan (Nordic Journal of Comparative and International Education (NJCIE), 2021)
Digital skills are one of the key competences outlined in The European Reference Framework of Key Competences for Lifelong Learning prescribed by the EU in 2006. Integration of digital tools and resources into the classroom results in more platforms for teaching and learning activities. Teacher training programmes prepare pre-service teachers with pedagogical competencies and skills necessary for their future practices. This paper shows that pre-service teachers could overcome the pedagogical challenges during COVID-19 teaching by updating their present and future classroom teaching strategies around digital literacy. To explore further how these new teaching circumstances are understood and reflected on by pre-service teachers, the researchers collected written reflections of 52 pre-service teachers in Norway using an open-ended survey about their digital integration experiences in their practicum. This paper offers analyses of the reflections inductively to reveal the teachers’ process of development of their classroom teaching strategies as influenced by new digitalisation-related experiences. The findings show low levels of digital integration according to the SAMR model but moderate to high levels of satisfaction among pre-service teachers of digital practices. In the light of these findings, this study offers pedagogical technological implications for teachers and teacher educators who work with teacher education curricula.